2021
DOI: 10.3390/polym13183090
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Nonwoven Polyethylene Terephthalate Textile into Thermal and Acoustic Insulation for More Sustainable Buildings

Abstract: The construction and building sector is responsible for a large share of energy and material used during the life cycle of a building. It is therefore crucial to apply a circular economy model within the process wherever possible to minimize the impact on the environment. In this paper, the possibility of producing thermal and acoustic boards from industrial nonwoven waste textile is studied and presented. The nonwoven polyester textile obtained directly from the production line in the form of strips and bales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…These results, under a standardized methodology, allow the material to be compared with other research, where it is important to highlight that the fire resistance of thermal insulation materials is not key, as, in general, it is the interior linings that provide the capacity to resist fire in the event of an incident. It is important for such materials to be self-extinguishing and not to generate toxic gases, which is why conventional materials mostly generate problems when combusting [56,60].…”
Section: Discussionmentioning
confidence: 99%
“…These results, under a standardized methodology, allow the material to be compared with other research, where it is important to highlight that the fire resistance of thermal insulation materials is not key, as, in general, it is the interior linings that provide the capacity to resist fire in the event of an incident. It is important for such materials to be self-extinguishing and not to generate toxic gases, which is why conventional materials mostly generate problems when combusting [56,60].…”
Section: Discussionmentioning
confidence: 99%
“…Recycled blended fabrics have also gained interest in thermal insulation applications. 81,99,100 Sakthivel et al 42 developed chemically bonded non-wovens from mechanically recycled cotton/polyester selvedge waste for automotive interior applications for thermal insulation purposes, and found that 50/50 cotton/polyester non-wovens showed better thermal insulation performance. Similarly, Sakthivel et al 81 characterized the insulation and acoustic properties of recycled PET/cotton nonwoven mats and reported that more than 70% good resistance was achieved.…”
Section: Mechanical Recyclingmentioning
confidence: 99%
“…In their study, Antolinc and Eleršič Filipič explore the use of industrial nonwoven textile waste for the production of thermal and acoustic panels. They convert polyester nonwoven textiles, obtained as strips and bales from the production line, into compact thermal insulation boards by shredding them into smaller segments and then compressing them using a hot press [18].…”
Section: Textile Membranesmentioning
confidence: 99%